Effect of Moringa oleifera L. Leaf Solution Concentration and Length of Storage on the Internal Quality of Duck Eggs (Anas platyrhyncos domesticus) - Silalahi, Melda Ramayana; Sayed Umar; Nurzainah Ginting; Ibrahim N Syaheera (Talenta Publisher, 2024)
Duck eggs have a delicious taste, are easily digested by the body, and contain quite good nutrition.However, duck eggs have a short self life. This study aims to determine the effect of the length of storage and concentration of Moringa leaf solution on the internal quality of duck eggs. This study was conducted in September-October 2023 at the Livestock Production Laboratory of Animal Husbandry Study Program, Faculty of Agriculture, Universitas Sumatera Utara. The design used in this study is a complete random design, factorial pattern, namely 4 concentration solution treatment (R0 = without soaking, R1 = 10%, R2 = 20%, R3 = 30%), 5 Treatment of Length of Storage (L0 = 0 days, L1 = 7 days, L2 = 14 days, L3 = 21 days, L4 = 28 days) with 2 replications. The parameters used in this study include the egg white index (albumen), the egg yolk index (yolk), the percentage of decreased egg weight and the degree of acidity (pH) of eggs. The results showed that the number of concentrations of 30% solution had a significant effect (p <0.05) on the albumen index, yolk index and pH, but did not affect the percentage of decreased egg weight. The length of storage has a significant effect on the internal quality of duck eggs. The treatment interaction is a significant effect (p <0.05) against the egg white index (albumen) and egg pH. Treatment with a 30% moringa leaf solution had better results for 28 days compared to treatment without soaking.